Оптимізація проведення практичних занять з лікарями-інтернами педіатричних спеціальностей - Курочкін, Михайло Юрійович; Курочкин, М. Ю.; Kurochkin, M. Yu. (Полтава: УМСА, 2015)
У статті описаний досвід проведення практичних занять з дитячої анестезіології та інтенсивної терапії з лікарями- інтернами педіатричних спеціальностей. Досвід багатьох країн світу показує, що результати лікування, а часто й життя людини залежать у першу чергу від своєчасного надання медичної допомоги. Наочно це проявляється при всіх невідкладних станах, що виникають під час раптових захворювань, травм та нещасних випадків, утому числі і в дитячому віці. Тому спеціалісту, що працює в будь-якій сфері охорони дитячого здоров’я, необхідно володіти навичками невідкладної допомоги дітям різного віку, особливо при критичних станах. Заняття побудовані за прикладом курсів Європейської Ради Реанімації, де звертається увага на роботу у команді під керівництвом лідера, максимальну наближеність до реальних клінічних умов, вміння швидко поставити синдромологічний діагноз та провести необхідний комплекс заходів при невід-кладних станах.В статье описан опыт проведения практических занятий по детской анестезиологии и интенсивной терапии с врачами-интернами педиатрических специальностей. Опыт многих стран мира показывает, что результаты лечения, а часто и жизни человека зависят в первую очередь от своевременного оказания медицинской помощи. Наглядно это проявляется при всех неотложных состояниях, которые возникают во время внезапных заболеваний, травм и несчастных случаев, в том числе и в детском возрасте. Поэтому специалисту, который работает в какой-либо области охраны детского здоровья, необходимо владеть навыками неотложной помощи детям разного возраста, особенно при критических состояниях. Занятия по-строены по примеру курсов Европейского Совета Реанимации, где уделяется внимание работе в команде под руководством лидера, максимальную приближенность к реальным клиническим условиям, умением быстро поставить синдромологический диагноз и провести необходимый комплекс мероприятий при неотложных состояниях. In the course of Pediatric Anesthesiology and intensive care of the Department for Pediatric diseases of the faculty of postgraduate education of ZSMU there are doctors-interns in pediatric Anesthesiology, as well as doctors-interns of related specialties: pediatricians, neonatologists, family doctors are trained Since the beginning of the 2012 at the course there were introduced methods of teaching of practical skills like in courses ALS (advanced course of «resuscitation»), which held the European Resuscitation Council in Krakow. The aim of this course is to introduce the concept of emergency teams studing and training of leaders and members of the these teams of proper treatment of cardiac arrest in adults, as well as the threat of cardiac arrest; Interns train to recognize patients with the increased risk of cardiac arrest, to identify the causes of emergencies, learn to prevent circulatory arrest and to resolved the problems that occur during cardiac arrest and breathing, interns learn elements of communication with members of the emergency team as well as the relatives of the patient, and to make decision in emergency situations. After passing the courses of ALS we introduced a similar principle of practical lessons with doctors-interns. At the beginning of session we formed a team led by the leader of this emergency team and selected the patient with acute illness. Doctors-interns are encouraged to collect the anamnesis with mother of patient (as usually it makes by the leader of the team), jointly put a syndromological diagnosis or preliminary diagnosis and discuss the plan further actions, in descending order of their urgency. However, there no access to the medical records of a pediatric patient for the members of the team, the conditions of the task include the ability to identify and carry out priority activities, which in real life is usually necessary to undertake, pending the results of additional studies. Later, the members of the team discussed the plan of examination and treatment of the child at the hospital stage, and after the discussion the team compares its findings with the medical history of the patient. Practical skills in critical conditions which threat to life such as cardiac arrest and stop breathing are training by interns on training apparatus on the same pattern, but with calculations of the time and this stimulates doctors-interns for a more dynamic work and increases their interest. Practical lesson consists of three stages. At the first stage the doctors-interns are offered to preview the video with the conducting of cardio - pulmonary resuscitation, performing the conicotomia and tracheal intubation, and other emergency procedures; at the second stage the leading teachers-experts in pediatric anesthesiology show to the doctors- interns a artificial lung ventilation with the help of the facial mask (ALV), direct laryngoscopy, tracheal intubation and mechanical ventilation directly during the operations in the ENT - department of the clinic (where all the surgeries are performed under general anesthesia with the use of muscle relaxants, tracheal intubation and mechanical ventilation); at the third stage all skills are practiced on training apparatus by interns. Particular attention is paid to ethics and deontological features of communication with relatives of pediatric patients in critical conditions. At the end of the session the teacher conducts the analysis of the actions of each member of the «team». The first question for every doctor-intern is: «What did you like in your actions in the treatment of the patient in the emergency?» The second question is: «Is it possible to change your actions next time?». This method of «correction of mistakes» involves minimal criticism of the doctor-intern by the teacher and encourages maximum capacity of the intern to analyze their knowledge and skills, attracted him to further work on their deepening. Thus, the experience of European colleagues made it possible to increase the efficiency of practical training with the doctors-interns of pediatric specialties, increase their interest to such practical trainings and to increase the confidence of future doctors in their abilities.
Оптимизация проведения практических занятий с врачами-интернами педиатрических специальностей
The optimization of practical lessons with doctors-interns of pediatric specialities
Keywords: оптимізація навчання; практичні заняття; невідкладні стани; лікарі-інтерни; оптимизация обучения; практические занятия; неотложные состояния; врачи-интерны; optimization of the practical lessons; emergencies; practical trainings; doctors-interns